Studi Ini Menganalisis Dampak Jumlah Penduduk, IPM, Partisipasi Angkatan Kerja, Pengeluaran Pemerintah, dan Kemiskinan Terhadap Pertumbuhan Ekonomi di Jawa Timur (2020-2023) - Yunita Lestari; Galuh Siti Dewi; Nadia Lailatus; Rifai Rahmadani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Economic growth is an important benchmark indicating the success of development in a region. This study was conducted to determine the influence of population, the human development index (HDI), labor force participation, government spending, and the poverty rate on economic growth in East Java Province during 2021-2023. Using quantitative methods and multiple linear regression analysis, secondary data obtained from the Central Statistics Agency (BPS) was examined to understand the relationship and impact of each variable on economic growth. Poverty rates have been shown to have a significant negative impact on economic growth, indicating that reducing poverty is essential for increasing growth, meaning that reducing poverty can drive economic growth. Meanwhile, population, HDI, labor force participation, and government spending showed a statistically insignificant effect on economic growth, although theoretically expected to have a positive impact. These findings emphasize the importance of poverty alleviation strategies as an integral part of efforts to increase economic growth in East Java, while also indicating the need for greater attention in managing other factors to achieve sustainable economic development.